Cerebral gray matter volume correlates with fatigue and varies between desk workers and non-desk workers - Putra, Handityo A.; Park, Kaechang; Yamashita, Fumio; Nakagawa, Yoshinori; Murai, Toshiya (Frontiers in Behavioral Neuroscience, 2022)
Chronic fatigue syndrome (CFS), a clinical entity of chronic fatigue, has been associated with a decrease in regional gray matter volume (rGMV). In this study targeting a large number of healthy middle-aged individuals without CFS, the relationship between fatigue perception and rGMV was investigated. Considering that the work setting is an environmental factor that influences fatigue perception among healthy individuals, the differences between desk workers and non-desk workers were investigated. Chalder Fatigue Questionnaire (CFQ) scores were used for perceptional evaluation of fatigue, and rGMV of 110 brain regions was adapted with Statistical Parametric Mapping 8 on 1.5 T magnetic resonance imaging results for the volumetric calculation of gray matter. The CFQ scores were negatively correlated with the right supplementary motor area and positively correlated with the right superior parietal lobule and left basal forebrain in all participants (n = 1,618). In desk workers and non-desk workers, the CFQ scores correlated with different regions and yielded different mechanisms of fatigue perception in the brain. Identifying the gray matter regions correlated with fatigue perception in healthy individuals may help understand the early stage of fatigue progression and establish future preventive measures.